Family and Community Medicine and Brazilian Society of Family and Community Medicine: who are we, 45 and 40 years later? - Anderson , Maria Inez Padula (2021)
In 2021, which marks the 40 years of the Sociedade Brasileira de Medicina de Família e Comunidade (SBMFC) and the 45 years of the specialty in Brazil, with its first medical residency programs, we release this special edition of the Revista Brasileira de Medicina de Família e Comunidade (RBMFC). It includes three interviews, bringing the perspective of people who in some way represent the past, present, and future of the specialty. We certainly had many Family and Community physicians to consult, but it would be impossible to have every one of them in this space. Our guests are listed and presented at the end of this editorial.